Djibouti : 2008 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that Djibouti's macroeconomic performance improved significantly, but inflation pressures are intensifying. Real GDP growth accelerated to 5.3 percent in 2007, driven mainly by foreign direct investment concentrated in the construction and port services. Executive Directors have welcomed Djibouti's strong economic growth driven by large foreign direct investments in the port and other key sectors of the economy. Directors have also emphasized the importance of maintaining the fiscal consolidation objective, with a view to controlling inflation and creating fiscal space to finance the poverty reduction strategy.